Microplastic Content in Water using The Bongo Net Sweeping Method in Koto Panjang Reservoir, Kampar - Rahmawati Rahmawati; Budijono Budijono; Eni Sumiarsih (Berkala Perikanan Terubuk, 2023)
Microplastics are currently a new source of pollutants and are considered the latest research in fresh waters compared to marine waters which have been studied for a long time. This study aims to determine the type and abundance of microplastics using bongo nets in the waters of the Koto Panjang reservoir. The research was conducted from April to June 2022 using a purposive sampling method. Water samples were extracted using 20% KOH and characteristic observations with an Olympus CX 21 binocular microscope. Statistical analysis was carried out using the one-way ANOVA test to determine the comparison of microplastic abundance at different locations. Identification results obtained 6 types of microplastics namely types of fiber, film, fragment, pellet, granule, and foam. The highest abundance was 103.111 particles/m3 in the fiber type, while the lowest abundance was 3.778 particles/m3 in the granule type.